Understanding creep mechanisms of a Cu-Cr-Nb alloy by testing under constant structure conditions. (1st January 2021) - Zhang, M.; Gibeling, J.C.
Abstract: Stress reduction creep tests conducted on a Cu-Cr-Nb alloy (GRCop-84) at 923 K have confirmed local dislocation climb to be the rate-controlling deformation mechanism. The activation energy of creep was measured to be consistent with that of self-diffusion in Cu matrix. An internal back stress of approximately -9 MPa was identified to act on the rate-controlling dislocations, which is believed to be the sum of the back stress for dislocation-particle interaction and the forward stress for dislocation-dislocation interaction. This back stress, however, does not lead to a true threshold in the framework of thermally activated dislocation motion. Graphical abstract: Image, graphical abstract